Methods of obtaining working or study models of children with cleft lip and palate: A systematic review (Research, Society and Development, 2023)
Objective: The aim of this study was to know the different methods used to obtain working or study models of children with cleft lip and palate. Materials and methods: A review of the literature was carried out to compile information on methods of obtaining working or study models of children with cleft lip and palate, for which an electronic search was carried out in various databases such as PubMed, Taylor and Francis, Pesquisa, Web of Science, Proquest, Scopus, Springer, Epistemonikos, Google Scholar and Ovid, applying inclusion and exclusion filters. Results: A first screening was performed leaving 180 articles; after this selection, duplicate bibliography was eliminated, leaving 145 articles, subsequently, all records were verified and 21 studies that did not meet the selection criteria were excluded, resulting in 25 articles suitable for this literature review. Conclusions: Through time, different materials and methods have been used to obtain study or work models in patients with cleft lip and palate in order to find new ways for the treatment, planning and intervention of the same condition; thus, knowing each one of them would facilitate their application with the aim of improving the quality and warmth in which the treatment is carried out, in addition, it is important to develop comprehensive treatments with effectiveness and efficiency, which will only be possible with adequate records of each patient.